Transcranial magnetic stimulation: A potential new treatment for depression associated with traumatic brain injury. (7th May 2015) - Reti, Irving M.; Schwarz, Noah; Bower, Aaron; Tibbs, Michael; Rao, Vani
Abstract: Background : Each year, more than 1.7 million Americans suffer a traumatic brain injury (TBI) and the lifetime prevalence of major depressive disorder following TBI is between 25–50%. There are no validated established strategies to treat TBI depression. Repetitive transcranial magnetic stimulation (rTMS) is a novel putative treatment option for post-TBI depression, which, compared with standard pharmacological agents, may provide a more targeted treatment with fewer side-effects. However, TBI is associated with an increased risk of both early and late spontaneous seizures, a significant consideration in evaluating rTMS as a potential treatment for TBI depression. Whilst the risk of seizure from rTMS is low, underlying neuropathology may somewhat increase that risk. Review : This review focuses on the safety aspects of rTMS in TBI patients. The authors review why low frequency rTMS might be less likely to trigger a seizure than high frequency rTMS and propose low frequency rTMS as a safer option in TBI patients. Because there is little data on the safety of rTMS in TBI, the authors also review the safety of rTMS in patients with other brain pathology. Conclusion : It is concluded that pilot safety and tolerability studies should be first conducted in persons with TBI and neuropsychiatric comorbidities. These results could be used to help design larger randomized controlled trials.